An enzyme-free photoelectrochemical glucose sensor based on coupling BiVO4 with gold nanoparticles. (April 2021) - Chen, Li; Miao, Lili; Chen, Yu; Gao, Yiming; Di, Junwei
Abstract: A cathodic photoelectrochemical glucose biosensor based on the Au nanoparticles (AuNPs) and BiVO4 modified indium tin oxide (ITO) photoelectrode was developed successfully. The prepared ITO/AuNPs/BiVO4 photoelectrode showed a large and stable cathodic photocurrent in the presence of oxygen as electron acceptor. Moreover, it could act as mimic glucose oxidase under visible light irradiation and catalytically oxidized glucose to produce gluconic acid and H2 O2 in the presence of O2 . Meanwhile, the cathodic photocurrent decreased markedly because of simultaneous combination of the glucose oxidation and consumption of oxygen. Under the optimized condition, a linear relationship between photocurrent decrease and glucose concentration was obtained over the range of 1 n M to 1 mM with a detection limit of 2.6 × 10 −10  M (S/N = 3). This PEC biosensor shows a good selectivity, stability, repeatability and high sensitivity. This work provides a promising method for constructing a new type of cathode photochemical biosensor based on nanomaterials. Highlights: The ITO/AuNPs/BiVO4 photoelectrode generated a large cathodic photocurrent in the presence of oxygen as electron acceptor. Under irradiation, AuNPs/BiVO4 acted like glucose oxidase to catalytically oxidize glucose. The ITO/AuNPs/BiVO4 photoelectrode exhibited high sensitivity for detection of glucose.